Mediation effects in the 'purchasing and supply management (PSM) practice–performance link': Findings from a meta-analytical structural equation model. Issue 4 (December 2016) - Foerstl, Kai; Franke, Henrik; Zimmermann, Friso
Abstract: Firm value chains have developed into global disaggregated supply chains. As a result, purchasing and supply management (PSM) has long been recognized as a strategic function capable of contributing to superior firm performance and ultimately to (sustained) competitive advantage. Still, empirical evidence of the 'PSM practice–performance link' is widely scattered, which leads to a limited understanding of the interplay of different PSM practices en route to buying firm performance. Based on a systematic summary of 99 independent empirical studies in meta-analytical structural equation modeling, we test alternative models of the 'PSM practice–performance link', thereby demonstrating how their effect is mediated. Grounded in resource-based theories, our results indicate that internal PSM practices fully mediate the effect of relational and transactional supplier-facing PSM practices on operational performance. Still, relational supplier-facing PSM practices directly affect business performance, while transactional practices' effect is fully-mediated. Furthermore, operational performance serves as a full mediator for the relationships between internal PSM practices on market and financial performance and the effect of operational performance on financial performance is partially mediated via market performance. Finally, we discuss the implications of our study from a practical, theoretical, and methodological perspective. Highlights: Testing alternative mediation models of the 'PSM practice–performance link'. 99 empirical studies are aggregated through meta-analysis in the light of resource-based theories. Internal PSM practices mediate the effect of supplier-facing practices on operational performance. Relational supplier-facing PSM practices exert a direct impact on business performance. We provide PSM executives with objective evidence of the most beneficial PSM practices.